To solve the equation \( 4(3x - 2) = -24 \), follow these steps in order:
-
Distribute the 4: Multiply \( 4 \) by each term inside the parentheses. \[ 4 \times 3x - 4 \times 2 = -24 \quad \Rightarrow \quad 12x - 8 = -24 \]
-
Add 8 to both sides: To isolate the term with \( x \), add \( 8 \) to both sides of the equation. \[ 12x - 8 + 8 = -24 + 8 \quad \Rightarrow \quad 12x = -16 \]
-
Divide by 12: To solve for \( x \), divide both sides by \( 12 \). \[ x = \frac{-16}{12} \quad \Rightarrow \quad x = -\frac{4}{3} \]
So the correct order is:
- Distribute the 4
- Add 8 to both sides
- Divide by 12
The final solution is \( x = -\frac{4}{3} \).